Elemental Composition of Soils Mixed with the Grape Molasses - Aslı Kurnaz; Şeref Turhan; Muazzez Gezelge; Aybaba Hançerlioğulları; Mehmet Atıf Çetiner (Turkish Science and Technology Publishing (TURSTEP), 2016)
Molasses, which is a traditional food substance obtained by boiling the fruit with local procedures and is abundantly eaten by Turkish people, are commonly produced from grapes. Zile, which is county of Tokat city placed in Central Black Sea region, is famous with molasses in Turkey. A special soil called as molasses soil containing CaO is added into to molasses in order to resolve acidification during production process. The purpose of this study is to determine the element concentration levels in grabe molasses soil samples collected from Zile by using energy dispersive X-ray fluorescence spectrometry (EDXRF). For this purpose, thirty-eight elements and eleven oxides were detected in molasses soil samples. The average concentrations of six major oxides (MgO, Al2O3, SiO2, K2O, CaO and Fe2O3) were found as 1.58%, 7.96%, 17.01%, 1.01%, 30.52% and 8.72%, respectively. Also, the average concentrations of three minor (Na2O, P2O5 ,TiO2) and two trace (SO3, MnO) oxides were found as 0.96%, 0.12%, 0.95% and 0.04%, 0.1%, respectively.
Keywords: S; Agriculture (General); Chemical Composition; Oxides; Agriculture; Zile; Molasses Soil; S1-972; EDXRF; 2. Zero hunger; 13. Climate action; 8. Economic growth; 14. Life underwater